Pengaruh Media Pembelajaran Daring terhadap Hasil Belajar PWPB Kelas XII RPL SMK N 1 Bukit Sundi - Resti Rahmi Khairati Costa; Latifah Annisa; Ambiyar Ambiyar; Deviana Ridhani (Departement of Mathematics Education, 2023)
This study aims to determine the effect of online learning (X) on learning outcomes in web programming and mobile devices (Y) subjects at SMK N 1 Bukit Sundi. This study uses quantitative research. The data collection technique uses a questionnaire which is distributed to students. The population in this study were all class XII students majoring in RPL SMK N 1 Bukit Sundi totaling 40 students. The number of samples in this study were 40 students. Data analysis used simple linear regression analysis through calculations with the help of the IBM SPSS Statistics 26 program. The results showed that